Exposição à nicotina durante o início do período pós-natal: vulnerabilidade ao estresse na vida adulta? - Pereira Júnior, Antonio Alves (2021)
Smoking is a public health problem and affects about one-third of the world's adult population, being considered the main preventable cause of diseases and premature deaths. The amount of nicotine found in women who smoke can reach triple the amount of serum, but the American Academy of Pediatrics does not include nicotine in the list of contraindicated drugs during lactation due to the lack of scientific evidence in the area. This study aimed to assess whether nicotine exposure during the early postnatal period in rodents due to greater vulnerability to stress in adulthood. For that, Swiss mice were exposed to nicotine (8 mg / kg / day) during the breastfeeding phase, between the postnatal days 4 (PN4) and PN17, through osmotic minipumps implanted in the mothers. The control group integrated a mini-pump containing 0.9% saline. In adulthood (PN65), the unpredictable chronic stress protocol was performed for 10 days, with the forced swimming test as one of the stressors. One day after the last stressor, the elevated plus-maze test was performed and then the animals were euthanized, the blood collected for quantification of corticosterone and the separate brain structures for quantification of the brain-derived neurotrophic factor (BDNF), PSD- 95, synaptophysin, and synapsin I. There was no change in serum corticosterone in any of the groups. The stress protocol promoted a decrease in the body weight of the mice and, in the elevated plus-maze test, an increase in the average speed. In animals exposed to nicotine and the stress protocol, there was an increase in grooming frequencies and head diving. Animals exposed to nicotine had an increased latency for immobility and a decrease in immobile time in the forced swimming test, and a reduction in BDNF levels in the cerebellum. In animals exposed to nicotine and/or stress, there was a decrease in BDNF in the striatum and PSD-95 and synapsin I in the brainstem. Groups exposed to stress or nicotine alone had an increase in PSD-95, synaptophysin, and synapsin I in the cerebellum.